PROFIL EKOSISTEM LAMUN SEBAGAI SALAH SATU INDIKATOR KESEHATAN PESISIR PERAIRAN SABANG TENDE KABUPATEN TOLITOLI - Adli, Andi (JSTT, 2016)
Sabang Tende Waters is one of the tourist sites and is often visited by tourists. So seagrass will be undergoing environmental degradation and presentation tutupannya also continues to munurun. There are several factors which led to pressure on the field tour, number of seagrass nearly 200 people every week so in monthly can reach 800 people. Therefore the condition of Sabang Tende as the location of the utilization of nautical tourism will experience pressure on ecosystems seagrass research needs to be done, then the profile of seagrass ecosystems as one indicator of the health of the coast. Exploiting the potential of the coast can improve the welfare of coastal communities, but in the absence of sustainable management, it will reduce the function of the coast. This research aim 1). Identify the types of seagrass, density, density and type of closure of seagrass in waters Sabang Tende., 2). It examines the factors that influence Community characteristics, composition, density, and distribution of seagrass in waters Sabang Tende., 3). Analyzing the public perception about the role/benefits of ecosystem health indicators as seagrass in waters across the coast Tende. Research using the method of observation, interview, koesioner, and biophysical surveys. Research results showed the kind of density on the station I namely 27.5 ind/12m2stasiun II: 12m2 ind/42, station III: 36.9 ind/12m2. Based on the results of the research conducted in the third observation station, the number and type of seagrass found different (not always the same), i.e. the most types found on the station I (natural zones) as much as 4 types, while on station II (residential zone) as 6 types, and III (zone tourist resort) is only found 5 types of seagrass. The physical and chemical conditions on the the station I, II, and III 7 pH, salinity of 30 0/00, while the II, III have a range of 320/00 and it shows that the percentage 48.8 % said that seagrass beds that is in sabang tende in stir by a tourist who is visiting and 29 % of respondents said that seagrass beds that is in sabang tende having the condition seagrass beds good.